Modos de fazer e dizer: a experiência citadina em Ensaios-Poético- Geográficos (encontros, polifonias e afetos) - Borges, Rafael Henrique Meneghelli Fafá (2021)
Provoking meetings, that was the challenge of this work. Encounters that transformed, mobilized experiences with and in the city. This action was motivated by our understanding that the other, as stated by Gilles Deleuze, "is the expression of a possible world", the possibility of experimenting with other ways of doing and saying a city other than our own; that is, the other as this double power of variation, both in the way of seeing and showing our city experiences. In this work, our efforts turned to the variation of how to say, to the way we show what is happening to us, because we understand that thought and action are intertwined; that is, transforming the way of saying-city also modifies the way we act in it and with it. In view of this, we appropriated the political-aesthetics present in some texts and authors to produce what we call poetic-geographic essays: textual experiments produced with intercessors (name given by Deleuze to meetings that mobilize thought to create), which they operate as enhancers of the exercise of writing in other ways about, with and from the city, in order to experience it in multiple discursive and experiential possibilities.